2017
DOI: 10.1016/j.biopsych.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Development of White Matter Microstructure and Intrinsic Functional Connectivity Between the Amygdala and Ventromedial Prefrontal Cortex: Associations With Anxiety and Depression

Abstract: Background Connectivity between the amygdala and ventromedial prefrontal cortex (vmPFC) is compromised in multiple psychiatric disorders, many of which emerge during adolescence. To identify what extent the deviations in amygdala-vmPFC maturation contribute to the onset of psychiatric disorders, it is essential to characterize amygdala-vmPFC connectivity changes during typical development. Methods Using an accelerated cohort longitudinal design (1–3 time points, 10–25 years, N=246), we characterized developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
155
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(175 citation statements)
references
References 116 publications
16
155
4
Order By: Relevance
“…Medications and psychotherapy that treat depression increase functional coupling between the amygdala and the striatum, thalamus, right frontal and cingulate cortex [52], likely resulting in increased PFC inhibition and regulation of amygdala responsivity. With this in mind, it is important to note that although data consistently shows altered amygdala-prefrontal cortex connectivity associated with mood and anxiety disorders, it is unclear whether that dysfunction is hypo-or hyper-connectivity [46]. Our results support the theory of weaker top-down amygdala inhibition in children who experienced higher prenatal maternal depression and show subsequent behavioural alterations, and provide evidence of a structural basis for previouslyobserved deficits in functional connectivity.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Medications and psychotherapy that treat depression increase functional coupling between the amygdala and the striatum, thalamus, right frontal and cingulate cortex [52], likely resulting in increased PFC inhibition and regulation of amygdala responsivity. With this in mind, it is important to note that although data consistently shows altered amygdala-prefrontal cortex connectivity associated with mood and anxiety disorders, it is unclear whether that dysfunction is hypo-or hyper-connectivity [46]. Our results support the theory of weaker top-down amygdala inhibition in children who experienced higher prenatal maternal depression and show subsequent behavioural alterations, and provide evidence of a structural basis for previouslyobserved deficits in functional connectivity.…”
Section: Discussionsupporting
confidence: 69%
“…Previous results from our lab, in an overlapping sample, suggested an accelerated pattern of development (lower diffusivity) in right frontal-temporal white matter in children exposed to greater second trimester depressive symptoms [24]. Indeed, other data has found that potentially accelerated development may predispose children to psychiatric conditions later in life [46][47][48]. This may be a product of timing and brain areas.…”
Section: Discussionmentioning
confidence: 55%
“…We will evaluate studies of ELA with this normative developmental pattern in mind; if children who have experienced adversity demonstrate greater negative connectivity for their age than children who have not, this would reflect accelerated development and if children who have experienced adversity exhibit more positive or less negative connectivity than comparison children, this would reflect delayed development. In contrast, studies investigating developmental patterns of connectivity at rest have been more mixed, with some studies demonstrating an increase in connectivity with age (e.g., Gabard-Durnam et al, 2014) and others demonstrating a decrease (Jalbrzikowski et al, 2017). Because a consensus has not been reached on the normative developmental pattern of amygdala-mPFC connectivity during rest, we focus only on papers that explore the associations of ELA with amygdala-mPFC connectivity using task-related functional connectivity.…”
Section: Study Inclusion Criteriamentioning
confidence: 99%
“…The highly conserved neurocircuitry connecting the mPFC and the amygdala plays a critical role in anxiety, and in the extinction of fear memories (Adhikari et al, 2015;Janak and Tye, 2015;Milad and Quirk, 2002;Phelps et al, 2004) and is abnormal in PTSD patients (Gilboa et al, 2004;Koenigs and Grafman, 2009). The PFC and amygdala undergo striking structural changes during adolescence (Jalbrzikowski et al, 2017), providing a biological basis that may underlie their unique vulnerability to the disruptive effects of obesity and the consumption of diets rich in saturated fats and sugars. Paralleling clinical data in humans (Geha et al, 2017;Riederer et al, 2016), we showed that DIO rats exhibit significant and partly irreversible microstructural alterations in mPFC regions and amygdalar nuclei associated with fear learning and fear extinction (Vega-Torres et al, 2018).…”
Section: Short Exposure To An Obesogenic Diet Attenuates Basomedial Amentioning
confidence: 99%